Cultural diversity and international law. In the field of human rights and identities - Yacoub, Joseph (Sens public, 2010)
This communication was submitted to the International Conference “Cultural Diversity, Multilingualism and Ethnic Minorities in Sweden” (Ambassade de France en Suède, Institut français, Stockholm, Sweden, 2-3 september 2009).The topic deals with “Cultural diversity and international Law”. The author tries to make clear the evolution of international law in matter of cultural diversity. In other words, the question is: How has the international law come to integrate cultural rights and diversity within its corpus?